The putative tumour modifier gene ATP5A1 is not mutated in human colorectal cancer cell lines but expression levels correlate with TP53 mutations and chromosomal instability. Issue 7 (3rd March 2009) - Seth, R; Keeley, J; Abu-Ali, G; Crook, S; Jackson, D; Ilyas, M
Abstract : Background: Both the putative modifier gene ATP5a1 and the tumour suppressor gene TP53 are involved in the regulation of apoptosis and may be involved in the development of colorectal cancers. Aims: To investigate the relationship between these genes in 16 colorectal cancer cell lines. Methods: Each gene was screened for mutation using high resolution melting analysis and sequencing. Expression of ATP5a1 mRNA was tested by quantitative PCR. Results: Sequence changes in ATP5a1 were found in 9/16 (56%) cell lines and consisted of mainly novel single nucleotide polymorphisms (SNPs) found in the 5′ UTR, introns 4/5/9 and exon 7. TP53 mutations were also found in 9/16 (56%) cell lines; these were consistent with previous reports. High levels of ATP5a1 expression were seen in cell lines with TP53 mutation compared with those with wild type TP53 (p = 0.02). Furthermore, an A→G change at the −18 position in intron 4 of ATP5a1 was significantly associated with increased gene expression (p = 0.0391). Comparison with genotype showed that cell lines with chromosomal instability (CIN) had significantly higher levels of ATP5a1 expression than those with microsatellite instability (MSI) (p = 0.02). Conclusion: Higher levels of ATP5a1 expression are associated with certain SNPs and with TP53 mutation. High expression also occurs in CIN and may facilitate tumour development along this pathway. Conversely, low levels of ATP5a1 expression may facilitate development of tumours with MSI.